Assessing cognition following petrol sniffing for Indigenous Australians. - Dingwall KM; Lewis MS; Maruff P; Cairney S (Australian & New Zealand Journal of Psychiatry, 2010)
Background: Chronic petrol inhalation can be associated with significant cognitive impairment. While rehabilitation programs can rely on such skills to educate clients and achieve treatment outcomes, cognitive function is rarely assessed on admission. This is particularly true for Indigenous populations where standard assessments are not appropriate. This paper describes a process for assessing cognition in Indigenous Australians. Two studies investigate firstly the demographic factors impacting on cognition for healthy Indigenous Australians and secondly the utility of the assessment process for detecting petrol sniffing related cognitive impairments. Methods: Study One assessed a naturalistic sample of healthy Indigenous Australians from the Northern Territory ( N = 206; mean age = 28.03) on computerised tests of psychomotor speed, visual attention, memory, learning, spatial awareness and executive functions. Multiple regression analyses determined the unique contributions of six factors (age, education, gender, familiarity with computers, regular long term cannabis use and locality) to the variance in performance for this group. Study Two examined group differences in cognitive performance on the same tests between healthy Indigenous Australians ( N = 96) and Indigenous petrol sniffers ( N = 50; both age restricted to < 26 years) while controlling those factors found to impact on performance from Study One. Results: Age, computer familiarity, and education significantly contributed to the variance in performance measures. While controlling these factors, petrol abuse was associated with poorer performance on complex tasks of psychomotor, visual attention, memory, learning, spatial awareness and executive function. Conclusions: This assessment process is useful for detecting substance abuse related impairments in Indigenous Australians and when using this assessment process, age and computer familiarity in particular should be controlled for.